Orphanage-Based Basic Health Protocol Education as an Effort to Form a Covid-19 Responsive Generation: Edukasi Protokol Kesehatan Berbasis Panti Sebagai Upaya Membentuk Generasi Tanggap Covid-19 - Muh. Kasim; Hendra Poltak; Muhfizar Muhfizar; Handayani Handayani; Nurfitri Rahim; Sri Wahyuni Firman; Dheni Rossarie; Nurul Huda; Yani Nurita Purnawanti (Politeknik Kelautan dan Perikanan Sorong, 2022)
The spread of COVID-19 is still very high in Indonesia, especially in Eastern Indonesia. Inadequate facilities and the presence of health workers are still the toughest challenges in dealing with the spread of this virus. The low awareness of health protocols has led to various clusters of Covid-19 transmission in various places, including the orphanage. Real actions of concern at the Orphanage were carried out by educating on health protocols to prevent the COVID-19 pandemic from spreading to the residents of the Orphanage. There were 28 health protocol education participants consisting of 24 girls and 4 caregivers at the Muhammadiyah Al-Amin Orphanage Sorong. Evaluation of the results of health protocol education by observing and monitoring health conditions where residents of the orphanage have used standard masks and physical distancing. In addition, the residents of the orphanage have also behaved in washing their hands before starting activities.